2022
DOI: 10.1038/s41598-022-21566-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex CRISPR/Cas9-mediated knockout of the phytoene desaturase gene in Coffea canephora

Abstract: Coffea canephora (2n = 2x = 22 chromosomes) is a species with extensive genetic diversity and desirable agronomic traits for coffee breeding programs. However, obtaining a new coffee cultivar through conventional breeding techniques may require more than 30 years of crossing cycles and selection, which hampers the effort of keeping up with market demands and rapidly proposing more resilient to climate change varieties. Although, the application of modern biotechnology tools such as precision genetic engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Among them, we may cite soybean ( Glycine max ) ( Jacobs et al., 2015 ), cassava ( Manihot esculenta ) ( Odipio et al., 2017 ), banana ( Musa spp.) ( Kaur et al., 2018 ), coffee ( Coffea canephora ) ( Casarin et al., 2022 ), grapevine ( Vitis vinifera ) ( Malnoy et al., 2016 ), rice ( Oryza sativa ) ( Lowder et al., 2015 ), wheat ( Triticum aestivum ) ( Upadhyay et al., 2013 ) and sweet orange ( Citrus sinensis ) ( Wang et al., 2014 ). And the list grows quickly, reaching species once intractable by conventional genetic methodologies.…”
Section: Crispr Technology In Agriculturementioning
confidence: 99%
See 3 more Smart Citations
“…Among them, we may cite soybean ( Glycine max ) ( Jacobs et al., 2015 ), cassava ( Manihot esculenta ) ( Odipio et al., 2017 ), banana ( Musa spp.) ( Kaur et al., 2018 ), coffee ( Coffea canephora ) ( Casarin et al., 2022 ), grapevine ( Vitis vinifera ) ( Malnoy et al., 2016 ), rice ( Oryza sativa ) ( Lowder et al., 2015 ), wheat ( Triticum aestivum ) ( Upadhyay et al., 2013 ) and sweet orange ( Citrus sinensis ) ( Wang et al., 2014 ). And the list grows quickly, reaching species once intractable by conventional genetic methodologies.…”
Section: Crispr Technology In Agriculturementioning
confidence: 99%
“…Breeding perennial plants is time-consuming, and the possibility to modify specific traits by editing target genes with no other potential change in the genetic background is very appealing. In coffee, gene editing studies available so far ( Table 3 ) are merely proof of concepts in C. canephora plants ( Breitler et al., 2018 ; Casarin et al., 2022 ). In both studies, PDS was used as a target gene and the CRISPR machinery was delivered to embryogenic callus by A. tumefaciens .…”
Section: Gene Editing Of Coffeementioning
confidence: 99%
See 2 more Smart Citations
“… 26 It also allows for simple screening of mutant lines. 27 , 28 Recent studies have shown the establishment of efficient genome editing using the PDS gene through the CRISPR/Cas9 system in several crops, including potato, 24 pea, 29 papaya, 30 coffee, 31 chickpea, 32 hop, 23 onion 25 and squash. 33 Nevertheless, the development of a biolistic-mediated CRISPR/Cas9-reagent delivery system using the PDS gene in chilli pepper has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%